Attitudes of outstanding students towards non-grade activities in Mafraq Governorate - Alkhawaldeh, Nayef Mohammad (Journal of Educational and Psychological Sciences, 2020)
The aim of this study is to identify the attitudes of students towards non classroom activities in the schools affiliated to the Directorate of Education of Qasbet Al-Mafraq and to identify their attitudes towards each of the non-class activities (cultural, sports and Art), In order to achieve the objectives of the study, the descriptive approach was used. The study population consisted of all outstanding students in the schools affiliated to the Department of Education and Education of the Al-Mafraq Brigade for the academic year 2018/2019. The study sample consisted of 173 of the 9th and 10th grade students (58% 9th grade, 42% 10th grade) the average account for students’ age was (15.4) and the standard deviation was (.05).The questionnaire was used as a tool for study after ascertaining its degree of sincerity and persistence, The results of the study showed positive trends towards the fields of activities The highest statistical significant activity was art and there weren't statistically significant differences between the attitudes of the students who were superior to the non-classroom activities due to grade variable (ninth and tenth grades),It has been recommended the following: doing more field research around this topic about non-class activities because there are some variables the study did not deal with them. Also we should reinforce the trends towards non- class activities through holding training courses, workshops and special seminar. Planning for a whole program around the topic of non-class activities and cooperate with parents, enhancing the school environment and offering the needed equipment.
Keywords: attitudes; highly-educated students; non-descriptive activities